Producer's messages as instruments of supranational slavic identity construction (on the case of a screen version of Gogol's novel «Taras Bulba») - Deyneko, A. (ХНУ імені В.Н. Каразіна, 2012)
The article presents the results of a comparative analysis of the Gogol's novel «Taras Bulba» and a screen version, produced by A. Bortko. The author highlights the producer's messages as the instruments of supra-national Slavic identity construction.
В статье представлены результаты сравнительного анализа повести Н.В. Гоголя «Тарас Бульба» и кинопродукта режиссера А. Бортко. Автор выделяeт режиссерские мессиджи как инструмент формирования наднациональной славянской идентичности.
Keywords: the Cossacks; Orthodoxy; producer's messages; Slavic identity